MecDoor / Ahmad Haziq Zamri ...[et al.] - Zamri, Ahmad Haziq; Rawi, Muhammad Asyraf; Mohd Sidik, Muhammad Atif; Rosman, Nur Nazmaniza Eliesya; A. Rahim, Nabilah Nur Atasha
There are many types of door in real life that serve one purpose to provide security by controlling access to the doorway. However, after undergoes some observations, it has been identified that most of the store owner uses the door to make the store more pleasing to the eye. Hence, the product known as the MecDoor is invented which is innovative of the common automatic door with some tweak on the system to make it environmentally friendly and more efficient. This product is focusing on users who deal with stores where it has the entrance that needs to be open and closed. In- store, there are many types of users other than normal citizen and some of them are kids, elderly and even handicap. The MecDoor comes with an automatic system where it can be open and closed without you need to touch the door itself where the scissor snake mechanism is the main part that responsible on moving the door to open and close. Other than that, the product comes with a dual door system which is the common size for most of the store.